PENGARUH KONDISI SOSIAL EKONOMI MASYARAKAT TERHADAP MINAT BERSEKOLAH DI YAYASAN TUNAS MULIA BANTARGEBANG KOTA BEKASI - Djihadul Mubarok (Develop: Jurnal Ekonomi Pembangunan, 2021)
The influence of the socio-economic conditions of parents on students' interest in school has been investigated at the Tunas Mulia Bantargebang Foundation, Bekasi City. The sample of this research is the parents of students as many as 30 respondents which are determined by random sampling of the total number of parents of students. This research is a quantitative study using a questionnaire instrument developed from an instrument grid. The data analysis technique used descriptive analysis. The results of this study indicate that: the economic conditions of the surrounding community, especially the parents/guardians of the Tunas Alam Mulia Foundation students, belong to the middle to lower scale, where the average community does not have a steady income.